혈소판 응집능에 미치는 인슐린의 in vitro 효과에 관한 연구 - 박철주; Cheol Ju Park; 조재현; Jae Hyun Cho; 강호철; Ho Cheol Kang; 선영덕; Young Duck Sun; 양승원; Seung Won Yang; 정민영; Min Young Chung; et al. (The Korean journal of medicine, 1996)
Objectives: It has been suggested that functional abnormalities of platelets play a role in the pathogenesis of diabetic macro- and microangiopathy. Platelets obtained from diabetic patients have been shown to exhibit increased sensitivity to aggregating agents. It was reported that insulin influence on platelet and the long term insulin deficiency might account for the enhanced platelet aggregability frequently observed in diabetic patients. Our aim in this study was to clarify the influence of insulin on platelets in vitro. Methods: We investigated the effects of insulin on platelets response by incubating PRP(platelet rich plama) at 37℃ with different concentrations of the insulin for 5 or 30 min before adding the aggregating agents. Insulin final concentratons were 40, 100μIU/ml, assuming that the basal insulin concentration of PRP is 10 μIU/ml. The responses of platelets to ADP(adenosine diphosphate) and collagen were examined under basal conditions and after the addition of insulin, and they were quantified as the maximal aggregation(M) and T1/2(time consumed to reach 50% of the maximal aggregation). Results: 1) The subjects aged 27.4±2.5(mean±SE) years with body weight 62.5±6.3 kg. 2) The maximal aggregation of the control platelet in response to ADP(60.3±2.7%) was significantly reduced after PRP incubation for 30 min with 40 μIU/ml insulin(52.7±2.7%, 100 μIU/ml insulin(48.7±3.2%) (p<0.01). 3) The T1/2 of the control platelet in response to ADP(30.9±1.9sec) was significantly increased after PRP incubation for 30 min with 40pIU/ml insulin (36.6 ±1.7sec), 100 p μIU/ml insulin(38.3±1.7sec) (p<0.01). 4) The maximal aggregation of the control platelet in response to ADP(60.3±2.7%) was significantly reduced after PRP incubation for 5 min with 100 μ IU/ml insulin(56.9±2.5%), PRP incubation for 30 min with 100 μIU/ml insulin(48.7+3.2%)(p<0.01). 5) The T1/2 of the platelet incubated for 5 min in response to ADP(31.9±2.1sec, 32.5±2.0sec) was significantly increased after 30 min of incubation(36.6 ±1.7sec, 38.3±1.7sec) at 40μIU/ml, 100μIU/ml insulin concentration(p<0.01). 6) The maximal aggregation of the control platelet in response to collagen (63.9±2.8%) was significantly reduced after PRP incubation for 30 min with 40 p IU/ml insulin(58.3±3.0%), 100μIU/ml insulin(55.1±3.3%) (p<0.01). 7) The maximal aggregation of the control platelet in response to collagen(63.9±2.8%) was significantly reduced after PRP incubation for 5 min with 100 μIU/ml insulin(57.8±2.9%), PRP incubation for 30 min with 100 μIU/ml insulin(55.1±3.3%)(p<0.01). Conclusion: Insulin reduces the platelet response to ADP, collagen in vitro, especially in 30 min PRP incubation at same concentration.